Rotating Drum Mixers - Harner III, Joseph P.; Behnke, Keith; Herrman, Tim J. (My University, 1995)
This publication provides information about the two types of drum mixers: single-action and double-action.
MF2053_1995_10
Keywords: MF2053; Equipment and structures; livestock; MF